A New Link Scheduling Algorithm for 60 GHz-WPAN Communication System - Wei Shi; Jingjing Wang; Hao Zhang; Yun Liu; Qiuna Niu; Chunlei Wu (International Journal of Distributed Sensor Networks)
With apparent advantages of several GHz license-free spectra, low power consumption, low-cost implementation of CMOS devices, and so forth, 60 GHz wireless communication technology becomes the first choice for short-range high rate wireless communication in future wireless personal area network (WPAN) and wireless local area network (WLAN). While different from common WPAN system with omnidirectional communication, 60 GHz-WPAN system generally adopts directional communication. In this paper, a device (DEV) interconnected mechanism of 60 GHz-WPAN based on switched beamforming technology is structured firstly. Without considering the directional transmission characteristic of 60 GHz communication, most of the 60 GHz-WPAN Medium Access Control (MAC) protocols fail to make full use of the high spatial reuse degree caused by directional communication. In this paper, an average time slot multiplexing allocation (ATSMA) algorithm based on space/time division multiple access (STDMA) solution is proposed, which allows concurrent transmission in a single time slot. The designed link schedule process includes common channel interference (CCI) probing scheme, link coexistence determination scheme, and link schedule algorithm. Extensive simulations are conducted in order to demonstrate the efficiency of proposed scheme. Simulation results demonstrated that the capacity gain is obvious using ATSMA algorithm, no matter whether under omnidirectional antenna or under directional antenna.